Datos primarios de: Galianthe holmneielsenii (Spermacoceae-Rubiaceae): A New Rheophilous Species from the Pacific Coast of Colombia and Ecuador - Florentín, Javier Elias (2023)
Datos primarios del artículo: Galianthe holmneielsenii (Spermacoceae-Rubiaceae): A New Rheophilous Species from the Pacific Coast of Colombia and Ecuador. Ilustraciones científicas, fotografías (lupa, microscopio electrónico de barrido MEB), distribución geográfica, etc.